In the wonderland of Peru: Machu Picchu nas páginas da revista National Geographic - Colombo, Micaela (Universidade do Vale do Rio dos Sinos, 2024)
The National Geographic magazine, founded in 1888, had the objective, throughout the 20th century, of making articles that would promote places and cultures considered different and exotic. Latin America, in this sense, was considered a vast camp for exploration. We propose here that the magazine, through funding recognition and exploration trips to the subcontinent, fed a north-american government political vector which, once the Spanish-American War (1898) ended, started a new phase in its relationships with Latin America. In this sense, this research’s purpose is to, through articles published in three editions of National Geographic (1913, 1915 and 1916) regarding the expeditions headed by Hiram Bingham to Machu Picchu, analyze the way in which Peru and its society are presented in the magazine. Despite the texts in the articles, as well as Bingham’s trip reports (1911 and 2010), being equally suitable for examination, we will be giving special attention to the almost 300 photographs that accompanied the articles. Since the 19th century the magazine would use photographs to illustrate its articles and try to capture the reader’s interest. Photography was seen as neutral and impartial, a producer of objective data about reality, which inferred more reliability to its content. From the “event” of Machu Picchu’s discovery on, we intend to show that, beyond mere illustration, the photographs in two of the previously mentioned editions of the magazine represented the way in which Latin America and, more specifically, Peru were seen and represented.
Keywords: Revista National Geographic; Machu Picchu; Yale Peruvian Expedition; Hiram Bingham; ACCNPQ::Ciências Humanas::História